IT Freelancing and Remittance Earnings in Bangladesh: Opportunities and Challenges. - Sabina Yasmin; K. M. Mahiuddin; Mohammed Nazmul Huq; Md. Riadul Islam Sakib (Journal of Science, 2026)
In Bangladesh, IT freelancing is becoming a cornerstone of economic progress, creating jobs for a large and enthusiastic young and tech-savvy populations while also increasing foreign earnings through remittances. This study examines how IT freelancing enhances employability and contributes to economic development and foreign currency inflows. Using both primary and secondary data collected from a diverse set of stakeholders, including individual freelancers, IT training centers, etc., the study identifies rapid sector growth, with annual earnings of over 1 billion. Yet, challenges persist, such as a gender disparity with women making up only 9% of freelancers, regional wage differences, and skill shortages in areas like AI, cybersecurity, and web development. Further challenges stem from inadequate rural infrastructure and unreliable payment systems. The study recommends investments in digital infrastructure, specialized training programs, and policies promoting gender inclusivity and freelancing as a career. These measures could boost Bangladesh’s global competitiveness and the economic potential of its IT freelancing sector.